Pelatihan Pemasaran Digital Pada UMKM di Desa Segaran Kecamatan Delanggu Kabupaten Klaten Jawa Tengah - Poppy Septinawati; Tasya Oktavia Ekawati; Yoga Surya Kusuma; Dian Vika Laurenshia; Agni Astungkara (Universitas Maritim AMNI Semarang, 2023)
Alongside the advancement of information technology, the marketing industry has grown pretty quickly. SMEs today have to implement new marketing techniques to promote their goods in the digital age. MSMEs exist in Segaran Village, Klaten, aswell. SMEs have the potential to succeed in Segaran Klaten Village because of the numerous artistic and cultural activities organized there. The issue, however, is that MSME players still have an inadequate understanding of the idea of digital branding. The community service team from UNIBA Surakarta provides digital marketing training for SMEs in Segaran Village as a result. This activity's implementation is carried out in stages. Through this activity it is expected to be able to provide an understanding of the function of digital marketing and have the ability to apply digital marketing. In the end, this activity is expected to be able to increase the economy of the people of Segaran Village with the role of digital marketing carried out by SME sactors in Segaran Village.